Sleep quality, mood and performance: A study of elite Brazilian volleyball athletes - Bevilacqua G.G.* (2016)
© Journal of Sports Science and Medicine.This investigation analyzed the relationships between sleep quality, mood, and game results in the elite athletes participating in Brazilian volleyball competitions. Participants (n = 277 elite Brazilian volleyball athletes, 214 (77.3%) men and 63 (22.7%) women) completed the Brunel Mood Scale (BRUMS) and reported their subjective sleep perception. Athletes with poor sleep quality reported higher scores for confusion compared to athletes with good sleep quality (p < 0.01, d = 0.43). In addition, athletes who lost their game at the time of evaluation showed higher tension (p < 0.01, d = 0.49) and confusion (p < 0.01, d = 0.32) levels compared to athletes who won their game. A regression analysis demonstrated that for each point increase in the confusion level, there was a 19.7% reduction in sleep quality. Multivariate analysis of variance indicated that athletes who slept well, and won their games, had lower tension levels. Further, our results indicated that the athletes’ mood associated with their success in the competitions. Therefore, in a competition, it is important that the athletes show good sleep quality, and use techniques and strategies to ease their mood variations.